Achievements of electro spinning chitosan using composite materials. (2022) - Surakasi, Raviteja; Mohana, J.; Louies Praveen, S.; Patil, Pravin; Karthick, R.; Alam, Md Irshad
Abstract: The electro spinning system depicts the transformation of an inorganic nano component or polymers into such another polymer or inorganic grid. An option is to electro spin a colloidal scattering. We've involved an assortment of strong Nano powders and polymers in our examination. Every one of the colloids that breezed through the assessment was electros pun. The little nanoparticles of the made nano fiber mats were contained by the polymeric nano fibers; in any case, the huge ones were identified sticking to the nanofiber mats. When contrasted with unadulterated polymeric nanofibers, the recommended technique could be used to make polymeric nanofibers with metal nanoparticles, which could have fascinating elements. As far as bioactivity, PCL/Ti nanofiber mats beat virgin PCL. The proposed approach can be respected in a game-changing strategy for assembling a development of electrospun nanofiber mats that beyond the realm of possibilities to expect to make utilizing current electrospinning techniques. The nano composite materials utilized in electrospinning are polymer-based, artistic, metallic, and other bioactive particles.